Implementasi Pembelajaran Fiqh pada Siswa SD (Studi Kasus SD IT Al-Muhibbin Cirebon) - Didi Mustahdi (Tihamah: Jurnal Studi Islam, 2023)
Fiqh is one of the subjects of Islamic religious education which has become a characteristic and is developed through a conscious effort to prepare students to live, understand, live and practice teachings, worship, and muamalah through teaching guidance or training activities. This type of research is field research or field research, namely research that is carried out intensively in detail and in depth on an organization, institution or certain symptoms. This research is descriptive, namely focusing on the current phenomenon being investigated by describing and classifying the facts or characteristics factually and accurately. This research is used to find out about what and how the state of a phenomenon or event and report it as it is. This study uses a qualitative approach, which is about the conditions in the field, researched, observed and based on the observations made. The fiqh subject aims to make SD IT Al Muhibbin students capable. Developing an interest in knowing and studying Islamic Shari'at to be responsive to the life of their environment, Growing an attitude of curiosity towards Islamic Shari'at, Growing awareness and responsibility in practicing Islamic Shari'at in everyday life, and Preparing them to attend education in schools Junior High School (SMP).